Anthropogenic Bush fires and environmental degradation in Makindu Sub-County, Makueni County Kenya - Mbuthi, Peter Maithya; Mbithi, Julius W.; Kamwaria, Alex N. (Research Journal in Advanced Social Sciences, 2024)
Anthropogenic fires are common in rural Africa as the indigenous people use fire to modify the environment for their survival.  Although human caused fire burning occurs as a significant traditional natural resource management practice and manifest a variety of ecological advantages, human initiated fires are viewed   by conservation authorities as destructible and a cause for environmental degradation. The study gains local perception from the local respondents of Makindu Sub County, Kenya near Chyulu Hills National Park on the cause of bush fires and their impact on environmental degradation. The study was   carried between October to January 2022 on various focused questionnaires, interview schedules, group discussions and observations were conducted among gender balanced respondents.  The study findings recorded ten reasons why they use fires justifying its use as a land management tool and most conspicuously acting as a catalyst of environmental degradation in the study area.  The study used descriptive research design to determine the causes of human induced bush fires and their recommends the use of adaptive collaborative management (ACM) where religious institutions, non-profit making organizations.  Government agencies like the NEMA, KWS and the local residents promote opportunities for shares learning are viewed as critical towards a better and a sustainable environmental conservation in Makindu Sub County, Kenya